Improved Quasi-Square-Wave Modulation Suitable for Isolated Modular Multilevel DC-DC Converter - Junliang Pan; Mingyu Wang (CSEE Journal of Power and Energy Systems)
The most commonly used modulation for an isolated modular multilevel DC-DC converter (IMMDCC) is quasi-square-wave modulation (QSWM). However, in order to realize soft-switching, QSWM-IMMDCC usually needs to increase the phase-shifting angle or reduce the voltage amplitude ratio, which will not only increase the conduction loss but also require more passive components. This paper proposes an improved quasi-square-wave modulation (IQSWM), which generates ripple current through the non-complementary output of the upper and lower arms. Compared with QSWM-IMMDCC, the ripple current can make IQSWM-IMMDCC realize soft-switching under the conditions of a smaller phase-shifting angle and larger voltage amplitude ratio. The decrease of the phase-shifting angle can improve the power factor of the AC link and reduce the inductance in the AC link, and the increase of the voltage amplitude ratio can increase the fundamental wave voltage of the AC output and reduce the capacitance of the sub-module. In addition, IQSWM can also adjust the ripple current according to changes in output power, thereby broadening the range of soft-switching. Finally, the ripple currents generated by multiple parallel IQSWM-IMMDCCs can offset each other, thereby preventing any impact on the DC output. The simulation results prove the correctness and effectiveness of IQSWM.